PubChem Protein, Gene, Pathway, and Taxonomy Data Collections: Bridging Biology and Chemistry through Target-Centric Views of PubChem Data. Issue 11 (15th June 2022) - Kim, Sunghwan; Cheng, Tiejun; He, Siqian; Thiessen, Paul A.; Li, Qingliang; Gindulyte, Asta; Bolton, Evan E.
Graphical abstract: Highlights: PubChem is a popular chemical biology information resource at the U.S. NIH. PubChem contains a wealth of data on chemicals related to biological entities. The PubChem Gene, Protein, Pathway, and Taxonomy collections are now available. These collections provide biological target-based data views of PubChem content. These collections are accessible both interactively and programmatically. Abstract: PubChem (https://pubchem.ncbi.nlm.nih.gov ) is a public chemical database at the U.S. National Institutes of Health. Visited by millions of users every month, it plays a role as a key chemical information resource for biomedical research communities. Data in PubChem is from hundreds of contributors and organized into multiple collections by record type. Among these are the Protein, Gene, Pathway, and Taxonomy data collections. Records in these collections contain information on chemicals related to a given biological target ( i.e., protein, gene, pathway, or taxon), helping users to analyze and interpret the biological activity data of molecules. In addition, annotations about the biological targets are collected from authoritative or curated data sources and integrated into the four collections. The content can be programmatically accessed through PubChem's web service interfaces (including PUG View). A machine-readable representation of this content is also provided within PubChemRDF.